Penerapan Teknik Pemotongan Rambut Gradasi sebagai Dasar Keterampilan Tata Kecantikan: Studi Kasus Kualitatif pada Mahasiswa Semester III - Fitriani, Farida; Nurhayati, Ifa; Angellita, Vivian Nur; Yuniarti, Wanda Anggi; Nefi, Rosa; Rafila, Firyal Usda; Azura, Octavina; Nabila, Ayesha; Elby, Queenasyifa Sakinata; Listiana, Ridainisa Dwi; Putri, Intan Aulia; Putri, Indah Selfiana; Rahmadiansyah, Hemalia Ayu; Munaf, Adinda Talitha Syahada; Hasanah, Selvi Hasnita; Khofifah, Anita Nur; Legawa, Kayla Putri (Universitas Negeri Semarang, 2025)
This study aims to analyze the application of graduation haircut techniques as a fundamental skill in beauty and hairdressing education among third-semester students of the Beauty Education program. This research employed a descriptive qualitative approach using a case study design. Data were collected through lecturer explanations during graduation haircut demonstrations, observations of students’ haircutting practices, and photographic documentation of haircut results. Data were analyzed using qualitative data analysis techniques consisting of data reduction, data presentation, and conclusion drawing. The results show that most students were able to apply graduation haircut techniques appropriately, particularly in maintaining the basic haircut line and volume formation. However, weaknesses were found in the symmetry between the left and right sides of the hair, indicating a need for repeated practice and more intensive guidance. The findings imply that mastery of graduation haircut techniques requires not only theoretical understanding but also continuous practical training supported by systematic evaluation. Strengthening these aspects is essential to prepare students to meet the technical and aesthetic standards demanded by the salon industry.